A Modification of random BIT stuffing insertion algorithm with modified RSA (RBMRSA) algorithm in data security applied in email text encryption. - Yuanah Marie S. Cruz, Rekhaela Vlain M. Navarro, Althea Coleen C. Salazar. 4 0 16; 5
ABSTRACT: The development in data transmission made it possible for individuals and organizations to communicate information around the world at real-time speed. As information is sent and received instantaneously, implementing data security technology like asymmetric cryptography secures transmission and ensures confidentiality, integrity, and authentication of the message. However, a trade-off existed between the total execution time and the security level of the cryptographic algorithm: a higher security level meant a slower execution time, and a faster execution time meant a lower security level. In this research study, a variant of the RSA algorithm called random bit-stuffing insertion algorithm with a modified RSA (RBMRSA( algorithm was enhanced and modified to improve the execution time and strengthen the security. RBMRSA strengthened the classical RSA algorithm through random bit insertion and increasing the number of primes used in generating the keys. This research study further enhanced the algorithm by increasing the number of primes used in generating the keys, increasing the key length to 2048-bit to meet the industry-accepted key length, and utilizing Extended Euclicdean Algorithm (EEA) and Chinese Remainder Theorem (CRT) to enhance the computational complexity and optimize the execution time of RBMRSA. The assessment of the algorithm included Big O Analysis and A valanche Effect as metrics and results were analyzed and compared with the 1024-bit key length RBMRSA. The results showed that the modified RBMRSA with CRT and EEA optimized the computational complexity of the algorithm in terms of encryption and decryption, and further improved the security performance.
Undergraduate Thesis : (Bachelor of Science in Computer Science) - Pamantasan ng Lungsod ng Maynila, 2024.
Keywords: 2 -- 0; 6; 20; 20; 2